A new approach to development - Michel, James H. (1997)
The relationship between developed and developing countries is changing. Aid donors are now reforming their policies so as to respect the ideas and opinions of developing countries and their peoples. This new approach is characterised both by ambitious goals and a realistic view of how they can be achieved. - Reproduced
Keywords: Foreign aid